(I)因为an=an-1+(n≥2,n∈N*),
所以an-an-1=n,设dn=an,
则dn-dn-1=n(n≥2,n∈N*),d1=1,
由累加法可得:dn=,故an=n2
∵Sn=(bn-1) ①,∴Sn+1=(bn+1-1) ②
②-①得Sn+1-Sn=(bn+1-bn)=bn+1,∴bn+1=-2bn
把n=1代入①式可得b1=-2,
∴bn=(-2)n
(II)由(I)可知cn=an=n2=n
①bncn=n•(-2)n
∴Tn=1•(-2)+2•(-2)2+3•(-2)3+…+n•(-2)n
-2Tn=1•(-2)2+2•(-2)3+3•(-2)4+…+n•(-2)n+1
两式相减得:3Tn=1•(-2)+(-2)2+(-3)3+…+(-2)n-n•(-2)n+1
=-n•(-2)n+1=-[1-(-2)n]-n•(-2)n+1
故所求数列的前n项和为:Tn=--(-2)n+1
②∵sin1=sin[(n+1)-n]=sin(n+1)cosn-cos(n+1)sinn
∴==sin(n+1)cosn-cos(n+1)sinn |
sin1cosncos(n+1) |
=[tan(n+1)-tann]
故所求数列的前n项和为:
An=[(tan2-tan1)+(tan3-tan2)+…+(tan(n+1)-tann)]
=[tan(n+1)-tann]